Theoretical study of metal-metal cooperativity in the homogeneous water gas shift reaction - Kuriakose, Nishamol; Kadam, Shantanu; Vanka, Kumar (Inorganic Chemistry, 2012)
The possibility of metal-metal cooperativity in improving the yield of the homogeneous water gas shift reaction (WGSR) has been investigated through full quantum mechanical density functional theory calculations. The calculations indicate that bimetallic catalysts would be likely to be more highly active than mononuclear metal-based catalysts for the WGSR. The results have implications for the design of improved WGSR catalysts in the future.

Can molecular cages be effective at small molecule activation? a computational investigation - Kuriakose, Nishamol; Vanka, Kumar (Inorganic Chemistry, 2013)
Several approaches have been investigated in recent years in the area of small molecule activation. The current work introduces a new concept in this field: that of molecular cages, containing only main group elements, serving to activate small molecules. Full quantum mechanical calculations employing DFT/SCS-MP2 methods indicate that recently synthesized Ga-N cage compounds would be excellent candidates for mediating in important reactions such as the catalysis of ammonia borane dehydrogenation. The current work therefore opens up exciting new possibilities in small molecule activation research.

Asymmetric transfer hydrogenation of imines in water/methanol co-solvent system and mechanistic investigation by DFT study - Shende, Vaishali S.; Shingote, Savita K.; Deshpande, Sudhindra H.; Kuriakose, Nishamol; Vanka, Kumar; Kelkar, Ashutosh A. (RSC Advances, 2014)
Asymmetric transfer hydrogenation of various cyclic imines proceeded efficiently with water/methanol co-solvent media in 20 min with excellent yields and enantioselectivities by employing Rh-TsDPEN catalyst and sodium formate as a hydrogen donor. The role of the co-solvent in enhanced productivity of the reaction was investigated by DFT. The mechanism for ATH of the imines has been discussed on the basis of the DFT study.

New insights into small molecule activation by acyclic silylenes: a computational investigation - Kuriakose, Nishamol; Vanka, Kumar (Dalton Transactions, 2014)
Recently synthesized acyclic silylenes have the potential to rival transition metal complexes in performing single site small molecule activation, which is significant because of the need to find cheap and green alternatives to transition metal complexes for this important class of reactions. However, the current computational study, a full quantum chemical investigation with density functional theory, demonstrates that undesired side reactions would be competitive in these systems during small molecule activation. The current investigation, in addition to shedding light on this problem, also provides solutions on how the undesired side reactions during small molecule activation can be avoided.

Can substituted allenes be highly efficient leaving groups in catalytic processes? a computational investigation - Kuriakose, Nishamol; Vanka, Kumar (Journal of Computational Chemistry, 2015)
There is considerable interest presently in the chemistry of allenes. The current computational investigation looks into the possibility of using allenes and their derivatives as leaving groups. As it is well known, leaving groups are significant in catalytic processes for generating the active site. A full quantum mechanical study using density functional theory shows that allenes and their derivatives can function as excellent leaving groups. Indeed, the calculations show that they can be several orders of magnitude more effective than existing ligands for this purpose. The modification of second generation Grubbs' catalysts with these ligands suggests that the allene ligand cases that would be most effective are those having electron withdrawing groups, especially those that have the potential for supramolecular interactions between the substituent groups in the free state. (c) 2015 Wiley Periodicals, Inc.
Keywords: allenes; carbones; Density functional theory; olefin metathesis; supramolecular interactions

Can main group systems act as superior catalysts for dihydrogen generation reactions? A computational investigation - Kuriakose, Nishamol; Vanka, Kumar (Dalton Transactions, 2016)
The protolytic cleavage of the O-H bond in water and alcohols is a very important reaction, and an important method for producing dihydrogen. Full quantum chemical studies with density functional theory (DFT) reveal that germanium based complexes, such as HCCMeArB(2)GeH (Ar = 2,6-(Pr2C6H3)-Pr-i), with the assistance of silicon based compounds such as SiF3H, can perform significantly better than the existing state-of-the-art post-transition metal based systems for catalyzing dihydrogen generation from water and alcohols through the protolysis reaction.